ECM Depletion Is Required to Improve the Intratumoral Uptake of Iron Oxide Nanoparticles in Poorly Perfused Hepatocellular Carcinoma - Yeow, Yen Ling; Wu, Jiansha; Wang, Xiao; Winteringham, Louise; Feindel, Kirk W.; Tirnitz-Parker, Janina E. E.; Leedman, Peter J.; Ganss, Ruth; Hamzah, Juliana (Frontiers in Oncology, 2022)
Improving tumour access for drug delivery is challenging, particularly in poorly perfused tumours. The availability of functional tumour blood vessels for systemic access is vital to allow drugs or imaging agents to accumulate in the tumour parenchyma. We subjected mice engineered to develop hepatocellular carcinoma (HCC), to treatment with tumour necrosis factor alpha (TNFα) conjugated to a CSG peptide (CSGRRSSKC). CSG binds to the laminin-nidogen-1 complex of the extracellular matrix (ECM) in HCC. When produced as a recombinant fusion protein, the TNFα-CSG functions as an ECM depletion agent via an immune-mediated mechanism to improve tumour perfusion. Tumour perfusion in HCC was dramatically improved after daily intravenous (i.v.) injection of 5 µg TNFα-CSG for five consecutive days. Following treatment, we assessed the tumour accessibility to accumulate an imaging agent, superparamagnetic iron-oxide nanoparticles (IO-NP). Here, we compared the passive delivery of an i.v. dose of IO-NP in HCC following ECM depletion after TNFα-CSG treatment, to the intratumoral accumulation of a comparable dose of CSG-targeted IO-NP in HCC with intact ECM. Magnetic resonance imaging (MRI) T2-weighted scans and T2 relaxation times indicate that when the tumour ECM is intact, HCC was resistant to the intratumoral uptake of IO-NP, even when the particles were tagged with CSG peptide. In contrast, pre-treatment with TNFα-CSG resulted in the highest IO-NP accumulation in tumours. These findings suggest poorly perfused HCC may be resistant to molecular-targeted imaging agents including CSG-IO-NP. We demonstrate that specific ECM depletion using TNFα-CSG improves nanoparticle delivery into poorly perfused tumours such as HCC.